Applying the Scholarship of Teaching and Learning: Pursuing a Deeper Understanding of How Students Learn - Michael Kiener, PhD, CRC (Park University, 2009)
The research discussed within is one example of how to move from scholarly teaching to the scholarship of teaching and learning. This transition began with a desire to better understand the teaching and learning process and evolved into the development of an empirically-based emerging theory called Mutual Engagement (ME). Mutual Engagement reinforces how group formation and a safe learning environment can benefit teaching and learning. Mutual Engagement embraces classroom research with the goal of making teaching and learning more visible for others to critique and to build theory and pedagogy.